Carbon storage potential and influencing factors of mangrove plantation in Kaozhouyang, Guangdong Province, South China - Kang, Li; Huamei, Huang; Ran, Yan; Shengpeng, Zhang; Di, Dong; Bo, Peng (Frontiers in Marine Science, 2025)
Mangrove plantation is a fundamental approach for the sustainable management of tropical and subtropical coasts to capture and store atmospheric carbon. However, it is unknown whether the carbon accumulation potential of planted mangroves is as much as that of natural mangroves. Moreover, the effects of tree species, forest age, and hydrodynamic conditions on carbon storage are still unclear. This study investigated the carbon storage potential and influencing factors for planted mangroves in Kaozhouyang, Huidong County, Guangdong Province. The Vegetation carbon stock was calculated by community parameters collected from field investigation, and ecosystem carbon stock was calculated by the sum of vegetation and sediment. The results showed that mangrove plantation significantly increased the carbon stock of the vegetation and soil (vegetation carbon stock = 9.9645.06 t C/ha; soil carbon stock = 70.37-110.64 t C/ha) compared with the nonvegetation mudflat (63.73 t C/ha). However, the ecosystem carbon stock of the planting sites was still lower than that of natural Avicennia marina (282.86 t C/ha), with the significant difference mainly reflected on the soil carbon stock (p < 0.05). Further results revealed that carbon accumulation was affected by forest age, tree species, and tidal level. The vegetation biomass/carbon stock gradually increased with forest age (p < 0.05), but the difference was not significant for soil carbon stock, which indicated that the carbon accumulation was mainly concentrated on the vegetation at the early stage of mangrove restoration. In addition, suitable habitat conditions (landward) and fast-growing species (Sonneratia apetala) are more beneficial to carbon accumulation. Our results suggest that mangrove plantations can achieve carbon storage and sequestration in vegetation and soil for increasing carbon sinks with suitable species selection and management.